Association between serum urate level and carotid atherosclerosis: an insight from a post hoc analysis of the PRIZE randomised clinical trial. Issue 1 (11th April 2022) - Tanaka, Atsushi; Toyoda, Shigeru; Kato, Toru; Yoshida, Hisako; Hamasaki, Shuichi; Watarai, Masato; Ishizu, Tomoko; Ueda, Shinichiro; Inoue, Teruo; Node, Koichi
Abstract : Objectives: Elevated serum urate (SU) levels are associated with arterial atherosclerosis and subsequent cardiovascular events. However, an optimal therapeutic target SU level for delaying atherosclerotic progression in patients with hyperuricaemia remains uncertain. The aim of this analysis was to assess an association between changes in SU level and carotid intima–media thickness (IMT) to examine whether an optimal SU concentration exists to delay atherosclerotic progression. Methods: This was a post hoc analysis of the PRIZE (programme of vascular evaluation under uric acid control by xanthine oxidase inhibitor, febuxostat: multicentre, randomised controlled) study of Japanese adults with asymptomatic hyperuricaemia. The primary endpoint of this analysis was an association between changes in SU levels and mean common carotid artery IMT (CCA-IMT) after 24 months of febuxostat treatment. Results: Among subjects treated with febuxostat (n=239), a total of 204 who had both data on SU and mean CCA-IMT at baseline and 24 months were included in this analysis. The mean baseline SU level was 7.7±1.0 mg/dL, and febuxostat treatment significantly reduced SU concentrations at 24 months (estimated mean change ‒3.051 mg/dL, 95% CI ‒3.221 to ‒2.882). A multivariable linear regression analysis revealed that a reduction in SU level was associated with changes in mean CCA-IMT values at 24 months (p=0.025). In contrast, the achieved SU concentrations were not associated with changes in mean CCA-IMT at 24 months. Conclusion: A greater reduction in SU, but not its achieved concentrations, may be associated with delayed progression of carotid IMT in patients with asymptomatic hyperuricaemia treated with febuxostat. Trial registration number: UMIN000012911